2022
DOI: 10.1590/1519-6984.240943
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a Coliphage AS1 isolated from sewage effluent in Pakistan

Abstract: The emergence of multi-drug resistant (MDR) bacterial strains, which are posing a global health threat has developed the interest of scientists to use bacteriophages instead of conventional antibiotics therapy. In light of an increased interest in the use of phage as a bacterial control agent, the study aimed to isolate and characterize lytic phages from sewage effluent. During the current study, bacteriophage AS1 was isolated from sewage effluent against E.coli S2. The lytic activity of phageAS1 was limited t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
7
1
Order By: Relevance
“…Previous studies revealed that an increase in temperature decreases the titer of phages [ 52 ]. However, numerous phages that have been studied thus far can survive high temperatures [ 53 ]. When phages are used to challenge bacterial cells, the multiplicity of infection is an important parameter to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that an increase in temperature decreases the titer of phages [ 52 ]. However, numerous phages that have been studied thus far can survive high temperatures [ 53 ]. When phages are used to challenge bacterial cells, the multiplicity of infection is an important parameter to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier investigations indicated that any rise in temperature lowers a phage's titer [39], [83]. However, several phages that have been investigated so far can withstand high temperatures [39], [84]. Phage ZCECO 5 maintained an excellent activity (~10 9 PFU/mL) after exposure to UV light for 40 min, but the phage was still active with titer approximately 10 6 PFU/mL after 60 min.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with previous studies [ 8 , 50 , 51 ]. On the other hand, Ullah et al (2021) [ 52 ] reported that the coliphage AS1 displayed optimum activity at high temperatures of 50 °C and 60 °C/30 min, and its infectivity reduced at 70 °C for the same exposure time. In 2007, Caldeira and Peabody [ 53 ] proposed that the disulfide bonds between capsid proteins may have a role to protect phages from thermal denaturation.…”
Section: Discussionmentioning
confidence: 99%
“…Wunsche et al (1989) [ 54 ] reported that the pH has an effect on the adsorption rate of phages on the host cell through changing the charge of capsid protein. Ullah et al (2021) [ 52 ] stated that most phages remain viable in a pH ranging from 5–9. In this study, there is no single pattern to evaluate the survivability of the two phages in different pH values.…”
Section: Discussionmentioning
confidence: 99%